Recovering international relations : the promise of sustainable critique - Levine, Daniel J. (Oxford University Press, 2012)
Surveying six decades of scholarship, Recovering International Relations suggests new ethical and methodological foundations for the study of world politics. IR is conceived as a vocation; one that must balance the insights of normative and empirical theory against each other to address a densely populated, heavily armed, and persistently diverse world.